Problemy powstające na tle stosowania niektórych rozwiązań prawnych wprowadzonych w Polsce w celu skutecznego wykrywania i dowodzenia nowych form przestępczości - Jaworski, Ryszard (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The institution of the “little crown witness” was introduced in the Polish Penal Code in 1997 to enable effective detecting and proving the most dangerous forms of crime. The witness in question is a suspect who may receive a more lenient sentence if he or she testifies about crimes committed by other persons. The institution is misused by the prosecution in Poland, as such witness’s testimony is interpreted as evidence, while it should be treated as information to be confirmed. Criminals abuse the institution to settle scores with rival gangsters and frequently accuse police officers and prosecutors of accepting bribes.
Keywords: Polska; przestępczość; wykrywanie przestępczości